It's not only a question of money! African Old Testament scholarship between the myths and meanings of the south and the money and methods of the north - Holter, Knut (Old Testament essays, 1998)
The article discusses Old Testament scholarship in sub-Saharan Africa from two points of view. First, its predilection for comparative studies, which allows the African experience ('the myths and meanings of the South') and the Old Testament to encounter and mutually illuminate each other. And secondly, its experience of being marginalised within the Western guild of Old Testament scholarship ('the money and methods of the North').